STRATEGIC MANAGEMENT OF ENVIRONMENTAL AND ECONOMIC SECURITY - KOSACH, Irina; KORMILO, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the conceptual principles of strategic management of environmental and economic security in the context of the national economy. It has been substantiated that the application of strategic management will allow to analyze and determine the trend of changes in the parameters of exogenous and endogenous influence on the state of ecological and economic security, innovativeness and relevance of measures of state influence. The purpose of the article is to form the conceptual foundations of the system of strategic state management of environmental and economic security. It has been determined that the strategic state management of ecological and economic security is an expression of a systemic approach to substantiating the principles and methods of ensuring the interaction of the elements of the management system, It should be defined as a set of management decisions aimed at ensuring the prospects for the implementation of organizational and economic mechanisms of state management. It has been noted that measures of strategic management of environmental and economic security are characterized by a clear sequence of implementation stages and a structured content of each stage, while the process of strategic management of security requires the formation of an appropriate management structure. The main tasks of the system of strategic management of ecological and economic security, functions and sequence of implementation of the specified process has been defined. The condition for the implementation of the strategic management is its integration into the complex mechanism of national security management, the action of which will contribute to the improvement of relations between all branches of state and regional administration. The key characteristics of strategic management of environmental and economic security in the context of a systemic approach are has been proposed such as integrity, complexity, synergy, functionality, heterogeneity, emergentity.